Temperature dependence of field‐responsive mechanisms in lead zirconate titanate. Issue 9 (1st June 2017) - Chung, Ching‐Chang; Fancher, Chris M.; Isaac, Catherine; Nikkel, Jason; Hennig, Eberhard; Jones, Jacob L.
Abstract: An electric field loading stage was designed for use in a laboratory diffractometer that enables in situ investigations of the temperature dependence in the field response mechanisms of ferroelectric materials. The stage was demonstrated by measuring PbZr1− x Ti x O3 (PZT) based materials—a commercially available PZT and a 1% Nb‐doped PbZr0.56 Ti0.44 O3 (PZT 56/44)—over a temperature range of 25°C to 250°C. The degree of non‐180° domain alignment (η002 ) of the PZT as a function of temperature was quantified. η002 of the commercially available PZT increases exponentially with temperature, and was analyzed as a thermally activated process as described by the Arrhenius law. The activation energy for thermally activated domain wall depinning process in PZT was found to be 0.47 eV. Additionally, a field‐induced rhombohedral to tetragonal phase transition was observed 5°C below the rhombohedral‐tetragonal transition in PZT 56/44 ceramic. The field‐induced tetragonal phase fraction was increased 41.8% after electrical cycling. A large amount of domain switching (η002 =0.45 at 1.75 kV/mm) was observed in the induced tetragonal phase.